Answer:
what whats the question so I can answer
Answer:
Step-by-step explanation:
3(x+7)=-36
x+7=-12
x=-19
I can’t seen the question so it is hard to answer
For this case, what we are going to do is use the following property:
Multiply an equation by a scalar.
In this case, the scalar will be:
k = -2
We have then that equation 2 will be:
k * (4x + y) = k * 1
-2 * (4x + y) = - 2 * 1
-8x-2y = -2
Answer:
The property that justifies this manipulation is:
Multiply an equation by a scalar.
385=15n+85
385-85=15n
300=15n
300/15=n
20=n